Life-history strategies and carbon metabolism gene dosage in the Nakaseomyces yeasts. Issue 2 (17th December 2015) - Legrand, Judith; Bolotin-Fukuhara, Monique; Bourgais, Aurélie; Fairhead, Cécile; Sicard, Delphine
Abstract : The Nakaseomyces clade consists of a group of six hemiascomyceteous yeasts ( Candida glabrata, Nakaseomyces delphensis, C. nivarensis, C. bracarensis, C. castelli, N. bacillisporus ), phylogenetically close to the yeast Saccharomyces cerevisiae, their representative being the well-known pathogenic yeast C. glabrata . Four species had been previously examined for their carbon assimilation properties and found to have similar properties to S. cerevisiae (repression of respiration in high glucose—i.e. Crabtree positivity—and being a facultative anaerobe). We examined here the complete set of the six species for their carbon metabolic gene content. We also measured different metabolic and life-history traits (glucose consumption rate, population growth rate, carrying capacity, cell size, cell and biomass yield). We observed deviations from the glycolytic gene redundancy observed in S. cerevisiae presumed to be an important property for the Crabtree positivity, especially for the two species C. castelli and N. bacillisporus which frequently have only one gene copy, but different life strategies. Therefore, we show that the decrease in carbon metabolic gene copy cannot be simply associated with a reduction of glucose consumption rate and can be counterbalanced by other beneficial genetic variations. Abstract : The decrease in carbon metabolic gene copy loss cannot be simply associated to a reduction of glucose consumption and can be counterbalanced by other beneficial genetic variations.